Animal Models of Middle Ear Cholesteatoma - Yamamoto-Fukuda, Tomomi (Hindawi Publishing Corporation, 2011)
Middle ear acquired cholesteatoma is a pathological condition associated with otitis media, which may be associated with temporal bone resorption, otorrhea and hearing loss, and occasionally various other complications. Cholesteatoma is characterized by the enhanced proliferation of epithelial cells with aberrant morphologic characteristics. Unfortunately, our understanding of the mechanism underlying its pathogenesis is limited. To investigate its pathogenesis, different animal models have been used. This paper provides a brief overview of the current status of research in the field of pathogenesis of middle ear acquired cholesteatoma, four types of animal models previously reported on, up-to-date cholesteatoma research using these animal models, our current studies of the local hybrid ear model, and the future prospect of new animal models of middle ear cholesteatoma.